Students Problem in Translating Pragmatic Equivalency - Fakhrurrazi M. Amin (JADEs Journal of Academia in English Education, 2020)
The objective of the study is to analyze students’ problem in pragmatic equivalence from Source Language to Target Language. The research applied qualitative method, data collected through questionnaire, interview, and observation. To process the data, interactive model of Miles and Huberman was applied to find out the result of the research. The subject of the study was the sixth semester students of English Education Department who are taken a translation class. The result showed that there are several problems faced by students on pragmatic equivalence from Source Language to Target Language in translation class. Those problems are coherence process, implicature/idiom, language structure, quality and velocity. And they faced the problem with many factors including on lack of understanding and mastering the material while translation learning occurs. Based on these finding it can be concluded that has faced the problem in pragmatic equivalence.